Legal Protection for Customers Resulting from Personal Data Leaks in Credit Agreements at PT Bpr Karya Sari Sedana (International Journal of Social Welfare and Family Law, 2026)
The economy of a country, including Indonesia, is a system that encompasses all production, distribution, and consumption activities occurring within the country. In the economy, problems often arise that can affect the welfare of society. The problem formulation in this study is: How is the regulation and supervision of both internal and external banks carried out to prevent customer personal data leakage in credit agreements? And how is the responsibility of BPR Karya Sari Sedana towards the leakage of customer debtor data? The research method used is empirical legal research. The conclusion in the study is the protection of customer data against personal data leakage by understanding the forms of supervision from both internal and external parties conducted by the banking institution and referring to the OJK regulations that have been established, in order to minimize the recurrence of similar incidents and allow the public to conduct transactions safely without worrying about their personal data. Leaked by irresponsible individuals. The responsibility carried out by the banking sector currently, namely the Financial Services Authority Regulation Number 22 of 2023 concerning Consumer and Community Protection in the Financial Services Sector, also regulates consumer protection in the financial services industry. Forms in policies related to regulations in the banking world ensure that the public does not worry about their personal data.